Fusion of Technology in Cochlear Implantation Surgery: Investigation of Fluoroscopically Assisted Robotic Electrode Insertion - Jablonski, Greg Eigner; Falkenberg-Jensen, Benedicte; Bunne, Marie; Iftikhar, Muneera; Greisiger, Ralf; Opheim, Leif Runar; Korslund, Hilde; Myhrum, Marte; Sørensen, Torquil Mcdonald (Frontiers in Surgery, 2021)
The HEARO® cochlear implantation surgery aims to replace the conventional wide mastoidectomy approach with a minimally invasive direct cochlear access. The main advantage of the HEARO® access would be that the trajectory accommodates for the optimal and individualized insertion parameters such as; type of cochlear access and trajectory angles into the cochlea. To investigate the quality of electrode insertion with HEARO® procedure, the insertion process was inspected under fluoroscopy in 16 human cadaver temporal bones. Prior to the insertion, the robotic middle and inner ear access was performed through the HEARO® procedures. The status of the insertion was analyzed on the post-operative image with Siemens Artis Pheno. The completion of the full HEARO® procedure including the robotic inner ear access and fluoroscopy electrode insertion was possible in all the 16 cases. It was possible to insert the electrode in all the 16 cases through the drilled tunnel. However, one case in which the full cochlea was not visible on the post-operative image for analysis was excluded. The post-operative analysis of the electrode insertion showed an average insertion angle of 507° which is equivalent to 1.4 turns of the cochlea and minimal and maximal insertion angles were recorded as 373° (1 cochlear turn) and 645° (1.8 cochlear turn) respectively. The fluoroscopy inspection indicated no sign of complications during the insertion.